Scripture as ‘One Book’: Origen, Jerome, and Cyril of Alexandria on Isaiah 29:11 - Crawford, Matthew R. (The journal of theological studies, 2013)
As a result of the research of F. M. Abel and Alexander Kerrigan, parallels between the exegetical works of Cyril of Alexandria and Jerome have long been known. In this article I highlight a previously unnoticed parallel which is perhaps the most striking instance yet discovered, since it demonstrates Cyril following almost exactly the wording of his predecessor. In exegeting Isaiah 29:11 both Jerome and Cyril interpret the ‘sealed book’ mentioned in the passage as Scripture which is ‘spoken by one Holy Spirit’ and so ‘is called one book’. Based on the cross-references cited by Jerome, I further argue that Jerome’s exegesis is indebted to Origen’s argument, found in book 5 of his Commentary on the Gospel of John, that the numerous individual books of Scripture are ‘one book’ in the divine Word who unites them. Thus, Origen’s exegetical labours continued to have influence beyond the outbreak of the Origenist controversy, even among those authors who otherwise took issue with his legacy. This instance highlights one way the patristic exegetical tradition developed, as later authors mined and redeployed the exegesis of their predecessors to meet new challenges in their own day.